INOVASI INFOGRAFIS PRODUK BANK SAMPAH SEBAGAI MEDIA EDUKASI LINGKUNGAN DI SDN SINDANGSARI - Indah Gita Cahyani; Rita Kusumah; Agisna Nurlatifah; Triana Gita Septiani; Fani Rahmawati; Agung Priatna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the environmental cleanliness conditions at SDN Sindangsari and design a Waste Bank program as an environmental education medium. This research employed a qualitative method with direct observation as the data collection technique conducted on May 7, 2026. The findings revealed that the school environment was not optimally clean, as indicated by scattered litter, the absence of waste segregation facilities, and low student awareness of environmental cleanliness. In addition, environmental education activities related to waste management were not carried out regularly. To address these issues, a Waste Bank program supported by educational infographics was designed to improve students’ understanding of waste management and environmental conservation. The program is expected to encourage clean living habits, increase student participation in maintaining environmental cleanliness, and create a cleaner, healthier, and more comfortable school environment.